Comportamento do eleitorado frente ao oportunismo dos governantes em anos eleitorais: uma análise para os estados do Brasil - Leite, Natanael Soares (2017)
The manipulation of economic variables by political agents in order to increase their chances of remaining in power has attracted the attention of researchers for some time, as well as the behavior of the electorate in the face of such manipulations. However, empirical studies on how the electorate behaves in the face of the opportunism and / or competence of rulers are rare in Brazil. Thus, the present study aims to investigate the behavior of the electorate, analyzing its capacity for observation and judgment through the signaling of the vote, that is, to identify if the voter can observe the signal of competence issued by the ruler, as well as, aims to investigate The effect of opportunism on the voting behavior of the electorate and, finally, to analyze if the voters present rational behavior. For that, the Brazilian states were used as observation from 1993 to 2010, using a methodological procedure to decompose the political cycles, trying to identify the parcels due to opportunism and competence. The results indicate that the economic senator is crucial in the voting behavior of the voter, who does not take into account the opportunism, nor the signaling of the ruler's competence. In addition, the results demonstrate a negative effect associated to the fact that the ruler belongs to the same party as the president, damaging his performance in the elections. These results reinforce the need for other studies that analyze in an alternative way the behavior of the electorate against the Brazilian politicaleconomic scenario, so that public policies can be created taking into account the peculiarities of the national political scenario.